Firm Performance: How to Define it, What Affects itand How to Deal with Measurement Challenges - Romanova, Regina (Journal of Economic Sociology, 2016)
How do some firms achieve superior performance and others fail? Much research has been devoted to this question in management, economic theory, and sociology. Nevertheless, due to the absence of a universal approach for conceptualizing firm success and differences in methodological assumptions, numerous studies have produced divergent findings. This has led to continuous debates on the meaning of market success, performance indicators, and measurement techniques. First, this paper addresses conceptual problems with application of the term “effectiveness” and analyzes the potential and limitations of an alternative construct―“performance.” In addition, we attempt to systematize current theoretical implications in the field of strategic management and sociological theories of organization. We focus on strategic management because performance-related questions are central in this academic discipline. Contrary to their intellectual ancestors in industrial economics, strategists pay closer attention to firm-level internal factors affecting firm performance. This paper examines two concepts central to strategic management: firms’ strategies and resources. We analyze strategic choice theory and contingency theory first, then turn our focus to core notions for a resource-based view—a dominant framework in strategy research. This article also addresses a sociological approach to the interpretation of firms’ high performance. A sociological understanding of the mechanisms behind performance variety concentrates on external factors (environmental effects). Firm survival and successful adaptation practices are studied in network, ecological, and institutional traditions in sociology. Finally, we discuss methodological challenges in performance research that require a combination of theoretical implications from both fields. In order to build an adequate theory about sources of performance variance, one should include micro- and macro-indicators and explore synergetic effects.